“Everything is believable”. Credibility of disinformation produced by using AI and the perception of Spanish communication students - García-Marín, David (2025)
news production processes and workflows. This is occurring simultaneously with a paradigm shift in news consumption patterns, in addition to the growing use of Artificial Intelligence (AI) within this environment. Based on studies regarding the perceived credibility of news and Cognitive Dissonance Theory, this research questions whether university students in the field of communication, who will be the future professionals in this sector, are able to distinguish between fake news created by AI from real news produced by humans. Methodology. A survey was carried out to measure the degree of truthfulness, accuracy, clarity and, consequently, the credibility of a total of six news stories created using ChatGPT as well as real news stories addressing health, migration and environment issues. Results and conclusions. It was found that the participants were not able to distinguish between fake news created using AI from true news made by humans in terms of truthfulness, accuracy, clarity, and credibility. Likewise, fake news was perceived as more truthful, accurate, and clear, even surpassing real news on all three variables. Original contribution. Thus, it is evident that the volume and speed of AI data processing, combined with human supervision and knowledge, can increase the chances of producing disinformation with a potential for manipulation unheard of until now.